Urban energy transition : from fossil fuels to renewable power - Droege, Peter (Elsevier, 2008)
Contemporary cities, initially shaped by the logic of the Industrial Revolution, have evolved into a worldwide urbanization force, driven by readily available and relatively cheap fossil fuel supplies. They now face major changes as the fossil fuel era rapidly comes to a close. The end of this era marks the emergence of a new urbanism based on a massive energy transformation, characterized by the growing embrace of efficiency programs, sustainable forms of distributed energy generation, and new urban structures, market approaches, technologies, and policies. If a soft landing from the fossil fuel high can be engineered geo-regionally or even globally, successful strategies to preempt or adapt to change in realizing a sustainable, post-fossil fuel future will have to entail revolutions in urban energy infrastructure, city form, urban development logic, community culture, and management. This volume will characterize the nature of this historical change, and explore current initiatives to avoid a human, environmental, economical and cultural cataclysm, and to stabilize the long-term outlook for our urban communities.